Variable radiological lung nodule evaluation leads to divergent management recommendations - Nair, Arjun; Bartlett, Emily C.; Rubtsov, Roman (The European respiratory journal, 2018)
Radiological evaluation of incidentally detected lung nodules on computed tomography (CT) influences management. We assessed international radiological variation in 1) pulmonary nodule characterisation; 2) hypothetical guideline-derived management; and 3) radiologists' management recommendations. - 107 radiologists from 25 countries evaluated 69 CT-detected nodules, recording: 1) first-choice composition (solid, part-solid or ground-glass, with percentage confidence); 2) morphological features; 3) dimensions; 4) recommended management; and 5) decision-influencing factors. We modelled hypothetical management decisions on the 2005 and updated 2017 Fleischner Society, and both liberal and parsimonious interpretations of the British Thoracic Society 2015 guidelines. - Overall agreement for first-choice nodule composition was good (Fleiss' κ=0.65), but poorest for part-solid nodules (weighted κ 0.62, interquartile range 0.50-0.71). Morphological variables, including spiculation (κ=0.35), showed poor-to-moderate agreement (κ=0.23-0.53). Variation in diameter was greatest at key thresholds (5 mm and 6 mm). Agreement for radiologists' recommendations was poor (κ=0.30); 21% disagreed with the majority. Although agreement within the four guideline-modelled management strategies was good (κ=0.63-0.73), 5-10% of radiologists would disagree with majority decisions if they applied guidelines strictly. - Agreement was lowest for part-solid nodules, while significant measurement variation exists at important size thresholds. These variations resulted in generally good agreement for guideline-modelled management, but poor agreement for radiologists' actual recommendations. - Tweetable abstract ERSpublications - click to tweetRadiological variations in pulmonary nodule evaluation translate into good overall agreement for guideline-modelled management, but poor agreement for radiologists' actual recommendations: 21% of radiologists can disagree with majority decisions http://ow.ly/bPOu30mcRYA
Gesehen am 09.12.2019
Roman Rubtsov is a member of the Lung Nodule Evalutation Group
Arjun Nair and Emily C. Bartlett contributed equally